TRANSFORMASI PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN SURAH LUQMAN AYAT 12-19 (Dimensi Revolusi Industri 4.0) - Adhitya Fajar Maulana; Masykur H Masykur H; Jaenal Abidin (LPPM STAI Ihyaul Ulum Gresik, 2026)
Education in Islam is important for the survival and safety of humans in this world and the hereafter. With that seeking knowledge is punished as an obligation that must be done by humans. Entering a new era of Islamic education is faced with a renewal challenge. Challenges such as rationalization, modernization, secularism, and positivism must be anticipated as soon as possible. Surah Luqman verses 12-19 provides a basic reference that must be carried out by education and applied according to the times. So with this the author is encouraged to conduct research and analyze the interpretation of surah Luqman verses 12-19 concerning the transformation of Islamic Education. The research approach in this thesis uses a qualitative approach. Then the method in this study is qualitative research which is library (Library Research). By studying and analyzing the Qur'an, especially the verses and terms related to the transformation of Islamic Education as primary data and commentary books, religious books as secondary data. Data collection techniques in this thesis using the documentation method. By examining various books, interpretations, journals and others related to the research theme. Then the data analysis process is carried out, namely, data reduction, data display, verification or drawing conclusions. Based on the research that has been done, the researcher obtains the results, namely; First. There are three aspects that must be transformed, namely in the inculcation of the values of aqidah, habituation of worship and sharia, and the application of morals in everyday life. Second, facing the Industrial Revolution 4.0, Islamic education is required to carry out renewal and modernization in terms of thinking and institutions as a measure of adjustment and welcoming progress.